Comparison of Tenoxicam and with Paracetamol at Right Mediolateral Episiotomies For Analgesia - Sapmaz, Ekrem; Altungül, Aygen Çelik (Fırat University, 2012)
Objective: The study is performed to compare the analgesic effect of tenoxicam supposotories and paracetamol pill for management of right mediolateral episiotomy repair. Materials and Methods: A total of 66 patients who gave birth vaginally with right mediolateral episitomy were randomly assigned to receive 40mg tenoxicam supposotories plus 3x1 placebo pill/po. (Group 1, n=33) or 3X500 mg paracetamol pill/po. plus placebo supposotories ( Group 2, n=33) after episiotomy repair and postpartum three days. Pain ratings were recorded before, first and 24 hours after medications. Verbal rating scale (VRS) and visual analog scale (VAS) used for pain record. Student T test, X 2 test, Mann Whitney U and Wilcoxon Rank Test used for statistical analysis and Spearman correlation analysis used for comparison between VRS and VAS (rs, n, p). Results: Tenoxicam supposotories is more effective analgesic than paracetamol pill for right mediolateral episiotomies pain. At G1 first hour VRS (3±0.5 point), VAS (6±1.1 point); at G2 first hour VRS (3.4±0.5point ) VAS (6.8±0.8 point) and this difference found statistically significant (p

Amaç: Sağ medyolateral epizyotomi sonucu ortaya çıkan ağrı üzerine tenoksikam süpozituar ile parasetamol tablet kullanımının etkilerinin karşılaştırılması. Gereç ve Yöntem: Sağ medyolateral epizyotomi ile doğum yaptırılan 66 hasta,randomize, prospektif, tek kör olarak iki gruba ayrıldı. Grup 1 (n=33): Tenoksikam süpozituar ve plasebo tablet, Grup 2 (n=33): parasetamol tablet ve plasebo süpozituar grubu. Epizyotomi tamirini takiben Grup 1’deki hastalara rektal yoldan 40 mg’lık tenoksikam süpozituar ve 3x1 plasebo tablet/po, Grup 2’deki hastalara ise 3x1 parasetamol 500 mg tablet/po ve plasebo süpozituar başlandı. Birinci ve 24. saatlerde Verbal rating skala (VRS) ve vizüel analog skala (VAS) kullanılarak ağrıları değerlendirildi. Verilerin istatistiksel analizinde X2,Student T, Mann Whitney U ve Wilcoxon Rank testleri kullanıldı (p
Sağ Medyolateral Epizyotomi Vakalarında Ağrı Kesici Olarak Tenoksikam ile Parasetamolün Karşılaştırılması